(untitled) (PANGEEA, 2025)
In my article I discuss the role of the textbooks in shaping the historical consciousness of the pupils in the Romanian school system during interwar years. I concentrate on the way in which, by means of school curricula December 1, 1918 was imposed as a lieux de mémoire in the consciousness of the future Romanian state citizens. Although, I elaborate mostly on selected textbooks used during the interwar time, I go beyond these chronological confines and refer to the textbooks during communist era and to those published during post-communist. My choice is motivated by the awareness that school textbooks were/are often used as political tools in building a national cleansed and official historical narrative. Implicitly, regime change brings mutations or at least variables when an historical event was/is interpreted, hence, revealing the influence of ideologies in shaping the reconstruction and the dissemination of the knowledges concerning the past of any national community. By crossing the interwar chronological borders, I would be able to highlight how authoritarian manifestations of political power, notable in all regimes I will refer to, tend to privilege a monolithic interpretation of the historical event(s). The simplest way to establish control was through the replacement of a variety of didactic literature with a unique textbook. As I show, this tendency is not linked, as generally expected, to the communist regime but has its antecedents